2004
DOI: 10.5713/ajas.2004.560
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetence Status of White Plumage Naked Neck versus Normally Feathered Broilers in Tropical Climate

Abstract: The study was undertaken to evaluate the effect of naked neck gene on mortality, cell mediated and humoral immune response in white plumage broiler population. The mortality of homozygous naked neck (Na/Na) broilers (11.71%) was comparatively lower than that of heterozygous naked neck (Na/na) (12.28%) and normally feathered (na/na) (13.59%) broilers. The humoral immune response was measured against (1% v/v) sheep red blood cells (SRBC) for total haemagglutinin (HA) antibody, 2-mercaptoethanol resistance (MER) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
3
9
0
Order By: Relevance
“…But HI titres to ND vaccination shows higher level for NaNa (5.10) followed by Nana and nana genotypes. Various reports (Patra et al, 2004;El-Safty et al, 2006;Fathi et al, 2005;Chatterjee et al, 2007; Galal, 2008;Rajkumar et al, 2010cRajkumar et al, , 2012b) on naked neck suggested higher humoral and CMI response in NaNa genotypes than Nana and nana ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But HI titres to ND vaccination shows higher level for NaNa (5.10) followed by Nana and nana genotypes. Various reports (Patra et al, 2004;El-Safty et al, 2006;Fathi et al, 2005;Chatterjee et al, 2007; Galal, 2008;Rajkumar et al, 2010cRajkumar et al, , 2012b) on naked neck suggested higher humoral and CMI response in NaNa genotypes than Nana and nana ones.…”
Section: Resultsmentioning
confidence: 99%
“…Immuno-competence traits: Humoral immunity was measured as antibody response against Sheep Red Blood Cells (SRBC) at 6 weeks of age (Patra et al, 2004). Haemagglutination Activity Asian J.…”
Section: Juvenile Body Weightsmentioning
confidence: 99%
“…In the present study, natural antibodies were also found present in Nicobari fowls, Vanaraja and all their F1 and F2 crosses (Tables 1Á3). Patra et al (2004) reported that the HA titres against SRBC of homozygous and heterozygous Naked Neck were comparatively higher than normally feathered broilers in a tropical climate. The mortality percentage of homozygous Naked Neck (11.71%) was lower compared to heterozygous Naked Neck (12.28%) and normally feathered broilers (13.59%) (Patra et al 2004).…”
Section: Resultsmentioning
confidence: 96%
“…Similarly, El-Safty et al (2006) observed that Nana laying hens had a significantly greater dermal swelling response to PHA-P compared to normally feathered hens. In broiler breeds, Patra et al (2004) reported significantly higher CMI estimates in Nana and NaNa genotypes compared to nana. Likewise, Alvarez et al (2003) showed that Nana chickens are the most resistant to Salmonella gallinarum (SG) infection and are better responders to vaccination with SG antigens compared to NaNa and nana sibs.…”
Section: Cell Mediated Immunitymentioning
confidence: 85%